Int. J. Biol. Pharm. Sci. Arch. 2021
DOI: 10.30574/ijbpsa.2021.1.2.0045
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants with anticonvulsant activities with emphasis on their mechanisms of action

Abstract: A large percent of the patients were controlled by the available antiepileptic drugs. The limited efficacy of antiepileptic drugs is still a matter of concern, >30% of patients showed refractory epilepsy and 30-40% suffered from antiepileptic side effects. Many kinds of medicinal plants possessed antiepileptic activity, and many researchers have focused on the efficacy of their crude extracts. This review discussed the medicinal plants with antiepileptic effect focusing on active ingredients and their mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In the last few decades there has been an exponential growth in the field of herbal medicine. Plants generally produce many secondary metabolites which are bio-synthetically derived from primary metabolites and constitute an important source of chemicals which are used as pharmaceuticals, agrochemicals, flavours, fragrances, colours and biopesticides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . The phytochemical analysis of Reseda lutea showed that the plant contained alkaloids, flavonoids, saponins, anthocyanin, glucosides and tannins, and the pharmacological studies revealed that it possessed antimicrobial, antiinflammatory, insecticidal, antiproliferative and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades there has been an exponential growth in the field of herbal medicine. Plants generally produce many secondary metabolites which are bio-synthetically derived from primary metabolites and constitute an important source of chemicals which are used as pharmaceuticals, agrochemicals, flavours, fragrances, colours and biopesticides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) . The phytochemical analysis of Reseda lutea showed that the plant contained alkaloids, flavonoids, saponins, anthocyanin, glucosides and tannins, and the pharmacological studies revealed that it possessed antimicrobial, antiinflammatory, insecticidal, antiproliferative and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%